HUMAN RESOURCE MANAGEMENT PRACTICES OF EMPLOYEE RETENTION IN RESEARCH UNIVERSITIES IN ISRAEL - Harpaz, Amir (Digital Repository of Theses, 2023)
Higher education systems, and universities among them, are experiencing high competition in recent years in retaining their employees. Universities are facing challenges from other competitive markets and the private sector. Failure to address and resolve retention issues can cause short- and long-term impacts on the organization’s performance. There is a lack of empirical data regarding Human Resource Management (HRM) strategies, perspectives, practices, and their effects on employee retention within universities in general and in Israel. This lack of data and understanding contributes to employee turnover. To date, no comprehensive, in-depth research has been conducted on the reasons for administrative staff turnover in universities in Israel. The purpose of this study is to explore and analyze the various human resource management strategies and practices used to maintain and improve employee retention of administrative and technical staff retention in research universities in Israel. This qualitative study utilizes individual interviews from research universities in Israel to allow the researcher to begin an inquiry into human resource management perspectives, strategies, and practices of employee retention in universities. The following primary research questions were addressed: 1. What are HRM professionals’ beliefs, perceptions, and attitudes about employee retention in their organizations? 2. What practices are HRM professionals implementing to reduce turnover and achieve employee retention? 3. According to HRM professionals, what retention practices and strategies are the most effective? 4. What are the main challenges for implementing retention practices? Four theoretical categories emerged from the data using Charmaz Grounded theory (Charmaz, 2014). 1) Lack of identification of retention as an organizational problem. 2) HRM lack of retention strategy. 3) HRM challenges. 4) Developing HRM retention practices. These categories presented a complex picture of the challenges faced by human resource managers in organizations, not only in their ability to retain employees but also in their ability to recruit new personnel for these organizations. Finally, this research could advance our understanding of employee turnover and retention in Israeli universities and enable the development, adoption, or modification of practices for employee retention. Continuation of future research may further help understand the trends of change in university employment patterns and allow efficient and effective strategic planning for employee retention in universities and organizations.